Implementation of Islamic Character in Madrasah Ibtidaiyah: Challenges and Opportunities Towards National Education Goals - La Ode Fajrul Islam Sabti; Jufri (Institute Journal and Publication Muhammadiyah University of Buton, 2024)
Character education in Indonesia is an important strategy in building a generation that is faithful, pious, has noble character, and has high integrity. This is in line with the goals of national education as stated in Law No. 20 of 2003. Madrasah Ibtidaiyah plays a strategic role in integrating Islamic character values, such as honesty, responsibility, and compassion, into the curriculum and daily educational practices. The implementation of character education in madrasahs is carried out through formal learning, habituation programs, and an Islamic school culture, which are designed to help students internalize character values ​​holistically. Character education in Madrasah Ibtidaiyah faces challenges such as limited resources, lack of family support, and the influence of globalization that can erode moral values. However, madrasahs also have great opportunities to overcome these challenges through the support of government policies, the role of teachers as role models, and collaboration with families and communities. The Islamic madrasah environment provides a strong foundation for the formation of student character that is relevant to the values ​​of the nation. This study uses a qualitative method with a library research to analyze the challenges and opportunities of character education in Madrasah Ibtidaiyah. The results of the study indicate that madrasahs can be an effective model of character education, producing a generation that excels academically and has an Islamic character. With synergy between schools, families, and communities, Islamic character education can contribute significantly to realizing national education goals, producing individuals who are intelligent, moral, and competitive in the global era.